Doing the twist, 1962. - (:unkn) unknown (Forsyth County Public Library)
WSJ 1-16-62 p.3.
Doing the twist, 1962. The photo accompanied an article describing the hazards of the dance.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth